RELIGIOUS EDUCATION - Kadankavil , Thomas (Journal of Dharma, 1984)
As life itself is often conceived as a journey towards maturity, growth into the maturity of faith or religion also is a journey. lr is a struggle each person has to undertake for himself, though in the process, one could turn out to be a helper in the religious education of his co-religionist. In this task of learning and teaching there is a radical particularity, namely, one can learn and teach that religion best in which one has been brought up from his childhood. The desire to take up the profession of teaching in general could spring either from a personal urge to share one’s knowledge with the younger and less informed members of his generation, or from the not so noble motive of seeking a livelihood. Education itself, however, is considered in the final analysis as a process of reaching out for transcendence, and an expression of that human quest. In this basic sense all good education can also be called religious.